Lighting installation of an office complex as a source of light pollution - Ściężor, Tomasz; Czaplicka, Anna (Instal, 2022)
Office complexes occupy more and more space in modern cities. Their areas are, at the same time, one of the best-lit urban elements. It is related both to the internal lighting of office spaces, as well as to the external lighting of parking lots or access roads. Moreover, advertising lighting is always associated with this type of objects. Renovation works carried out in one of such complexes in Kraków (Poland) allowed for the unique research allowing to determine how the various components of its lighting affect the individual categories of light pollution. The correct construction of all light sources was found, but in part of the complex, the phenomena of excessive lighting and glare associated with advertising panels were found. However, the main problem is the reflection of too much light by bright surfaces, especially pedestrian routes, which significantly affects the brightness of the artificial sky glow of Kraków.